2003
DOI: 10.1159/000072077
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up (5–20 Years) after Uterine Ventrosuspension for Chronic Pelvic Pain and Deep Dyspareunia

Abstract: Objective: To examine the long-term outcome of patients undergoing uterine ventrosuspension for chronic pelvic pain and deep dyspareunia. Methods: Eighty-two patients, presenting with retroverted uterus, pelvic pain and deep dyspareunia, underwent uterine ventrosuspension by laparotomy or laparoscopy during the period from 1981 to 1996. Only patients (56) with no pelvic pathologic condition, as identified intraoperatively, participated in the study. At the beginning of the year 2002, 41 out of 56 patients (73.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…In a review article by Daniell and Lalonde [13] , the value of LUNA for the treatment of pelvic pain and dysmenorrhea was further validated. In the current study, we have found a promising role of LUNA for the treatment of deep dyspareunia and had comparable effectiveness with uterine ventrosuspension published by Halperin et al [6] . At the last follow-up visit, the patient was satisfi ed with the surgical result, and the objective evaluation (by VAS score and revised Sabbatsberg Sexual Rating Scale) showed relatively good improvements in the symptoms of deep dyspareunia and primary dysmenorrhea.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In a review article by Daniell and Lalonde [13] , the value of LUNA for the treatment of pelvic pain and dysmenorrhea was further validated. In the current study, we have found a promising role of LUNA for the treatment of deep dyspareunia and had comparable effectiveness with uterine ventrosuspension published by Halperin et al [6] . At the last follow-up visit, the patient was satisfi ed with the surgical result, and the objective evaluation (by VAS score and revised Sabbatsberg Sexual Rating Scale) showed relatively good improvements in the symptoms of deep dyspareunia and primary dysmenorrhea.…”
Section: Resultssupporting
confidence: 83%
“…So far, there have been very few articles about the specifi c treatment for deep dyspareunia. The two surgical procedures which have been mentioned in the literature for the treatment of deep dyspareunia were laparoscopic uterosacral ligament ablation (LUNA) and uterine ventrosuspension [5,6] . In Vercellini's article, LUNA was originally performed to treat dysmenorrhea associated with endometriosis, and, accidentally, LUNA was found to have effi cacy for deep dyspareunia.…”
Section: Introductionmentioning
confidence: 99%
“…Even studies on ventrosuspension for treatment of retroverted uterus and chronic pelvic pain have an unacceptably high failure rate. Long-term follow-up of 5-20-year outcomes of laparoscopic uterine ventrosuspension approximates a success rate of 50% [27,28]. A good understanding of pelvic anatomy shows that the round ligaments play no role in uterine support or suspension [7].…”
Section: Resultsmentioning
confidence: 97%
“…However, due to the greater association with prolapse, women with the retroverted uterus are more likely to experience pelvic dragging sensation or pain, sacral backache (due to taut or turgescent utero-sacral ligaments [13]) or, eventually, a more obvious lump. It is well recorded that the anteriorly placed cervix is far more likely to be impinged upon with intercourse [7], especially if it is prolapsing, causing dyspareunia on deep penetration.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[6]), (c) pelvic pain and dyspareunia treated with laparoscopic ventrosuspension (15 papers, e.g. [7]), (d) increased difficulties with embryo transfer (4 papers, e.g. [8]), (e) issues regarding the insertion and performance of IUDs and diaphragms (3 papers, e.g.…”
Section: Introductionmentioning
confidence: 99%